Active SAR Antennas: Design, Development, and Current Programs - P. Capece (International Journal of Antennas and Propagation)
The paper presents the design guidelines for Active SAR Antennas followed for the development of COSMO Sky Med SAR Antenna Subsystem. They have brought to define the antenna architecture, the RF, and electrical requirements for all the antenna RF, digital and power units, taking into account the available technologies and achievable performance. The antenna design is described for what the main subsystems is concerned, such as RF, power, digital, including mechanical and thermal aspects. Finally the paper reports also a brief description of the most recent development carried out in Canada and in Europe in the last ten years, including the on-going programs.